Insect physiological ecology : mechanisms and patterns - Chown, Steven (Oxford biology readers., 2004)
Insects exhibit incredible physiological diversity, making them ideal model organisms for the purpose of this book. The authors draw together the central issues in physiology (nutrition, water balance, temperature, etc.) treating each in sufficient detail to give researchers a broad update in summary form.